Analisis Perspektif Generasi Milenial Tentang Perkawinan Kristen - Hotma Tutur Romauli Br Aritonang; Rencan C. Marbun; Herdiana Boru Marbun (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This study aims to examine the perspective of the millennial generation on marriage in Dolat Rayat Village, Dolat Rayat District, Karo Regency. The research method used is descriptive qualitative, involving six informants consisting of millennials who have experienced divorce. The results of the study indicate that the millennial generation views marriage as a union of two individuals with the aim of obtaining affection, attention, and support and forming a harmonious family. However, there are several factors that cause conflict in marriage, including lack of effective communication, interference from third parties such as in-laws or other relatives, and economic problems. In addition, roles and responsibilities in the household are often still one-sided. The greatest source of happiness in marriage is centered on the mutually supportive relationship of the couple, and the presence of children is also considered important. Although some informants acknowledge the benefits of premarital counseling, its implementation is still limited and is not always applied in overcoming problems such as egoism and family interference. The conclusion of this study shows that there are differences in perspective according to the millennial generation on marriage with marriage based on the Bible, where the glory of God should be the main goal of marriage, not happiness. This study suggests improving communication, limiting third-party interference, clear division of responsibilities, premarital counseling, and focusing on economic independence as an effort to strengthen marriages among the millennial generation.